2005
DOI: 10.1016/j.cvex.2004.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Viral diseases of ferrets

Abstract: Distemper and rabies vaccination are highly recommended because of the almost invariable fatal outcome of these conditions. Vaccination should constitute an important part of a ferret's preventative medicine program. With the current and anticipated development and licensing of new vaccines, practitioners are invited to gain awareness of the latest vaccine information. Establishment of a practice vaccination protocol with regards to the site of administration of rabies and distemper vaccines is paramount to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 60 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…It is likely to be safe, but has not been verifi ed satisfactorily yet. A suitable vaccination pattern involves primary vaccination at eight weeks of age with subsequent double revaccination at 3-week intervals followed by annual revaccinations (Quesenberry and Orcutt 2004;Langlois 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is likely to be safe, but has not been verifi ed satisfactorily yet. A suitable vaccination pattern involves primary vaccination at eight weeks of age with subsequent double revaccination at 3-week intervals followed by annual revaccinations (Quesenberry and Orcutt 2004;Langlois 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination in ferrets is associated with nausea, vomiting, diarrhoea, erythema and fever. Ferrets should therefore be monitored for at least 30 minutes after vaccination (Langlois 2005). Should an undesirable post-vaccination response occur, administration of an antihistaminic (diphenhydramin chloride) is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The infection was firstly found in ferrets, which is a wildlife reservoir. It becomes a big topic to be considered [8,9]. In fact, since the discovery of first case in 2012 and confirmation in 2013, it has been concluded that the possible source of rabies in Taiwan of China might be from mainland.…”
Section: Emerging Rabies In Taiwan Of China: the Revisit Of Old Diseasementioning
confidence: 99%